Developing sustainable museums through ‘greening’: a case study of the Zimbabwe Military Museum - Chitima, Simbarashe Shadreck (LANGAA RPCIG, 2021)
Developing sustainable museums through ‘greening’: A case study of the Zimbabwe Military Museum Simbarashe Shadreck Chitima Introduction We often hear scary news in the media concerning how greenhouse gas emissions are affecting the ozone layer and giving rise to global climate temperatures. Resources are getting depleted day by day and it is clear that the world is experiencing an environmental crisis that affects all regions of the world, society as well as the operations of organisations (Byers, 2008; Brophy and Wylie, 2008). This is threatening the viability of Earth as a habitat for stable human society and biodiversity. According to Zimbabwe’s Environmental Management Act of 2002 the environment is taken to mean the natural and man-made resources occurring in the lithosphere and atmosphere, air, water, soil and living organisms and the interaction between them. Further the ecosystem, economic, social, cultural or aesthetic conditions contribute to the value of the environment. Unfortunately it is sad that humans are responsible for destroying the planet through the processes and effects from the extraction of natural resources and the manufacture of products from those resources (Worts, 2004). Currently in Zimbabwe, it has become normal to hear of how power shortages affects water supply, company operations and how certain companies are ignorantly disposing of wastes in rivers and contaminating drinking water (Mwando, 2008, 223 Chenga, 2014). Zimbabweans are now used to hear or read about the closure of companies due to high operational costs, shortage of basic needs in grocery shops, plunder or depletion of natural resources (Mtomba, 2014). In order to prevent this crisis humans need to change their behaviour (Worts, 2006). It is not surprising that many of the challenges we face as humans emanate from this environmental crisis. Museums have the capacity to respond positively to this crisis by incorporating sustainable practices in their operations, programming and communicating with the public. If museums don’t actively resist this damaging activity, it could well be argued that they have failed in their duty of protecting heritage. The contribution of museums goes far beyond simply holding onto heritage for the future but many of museums’ roles and characteristics position them to be facilitators of the change that leads to a culture of sustainability. First, museums preserve and transmit patrimony, or objects in a museum’s collection, in perpetuity. To museums, the natural environment is patrimony and worthy of conservation (Scheiner, 1997). A culture of sustainability represents an individual and collective commitment to recognize the value of humanity’s common natural and cultural heritage (De Varine, 2006). Museums in Zimbabwe are a true reflection of a troubled environment. There are going through hard times to sustain themselves and the resources availed to them by government are not enough. This has seen collections in their custody deteriorating to unprecedented levels and some programmes being shelved till funding is available. This paper argues that if museums in Zimbabwe are to survive and be relevant in this globalised environment they have to adopt green practices. Museums can play a critical role in moving the communities they serve towards a more sustainable future (Brophy and Wylie, 2008). Museums in Zimbabwe can respond to this environmental crisis by incorporating green practices into their operations and programming (Byers, 2008). By going green 224 museums have a lot to benefit. Benefits include positively impacting the environment, increasing public trust, engaging communities, gaining a competitive advantage, attracting new audiences as well as financial savings. Going green enables a museum to connect to a deepening eco-consciousness among the young people who are our future audience and supporters (Sutter, 2006, Worts, 2006; Wylie and Brophy, 2008). Since museums exist to serve the public they have an obligation to play a role in the protection of the ecology. The pledge to protect the environment by governments and their institutions is not something that started yesterday. In fact conferences on environmental protection have been held since 1972 with the Conference on Human Environment, Bruntland Commission in 1987, United Nations Conference on Environment and Development in 1992, Earth Summit+5 in 1997, World Summit on Sustainable Development in 2002 and the Rio+20 in 2012. The United Nations Conference on Sustainable Development (Rio+20) held in Rio De Janeiro in 2012 should provide museums with the necessary footing to seriously pledge efforts to the protection of the environment. The essence of the Rio+20 conference was that if we are to leave a liveable world to our children and grandchildren, the challenges of...